Piloting a Text Message–based Social Support Intervention for Patients With Chronic Pain: Establishing Feasibility and Preliminary Efficacy. Issue 6 (June 2015) - Guillory, Jamie; Chang, Pamara; Henderson, Charles R.; Shengelia, Rouzi; Lama, Sonam; Warmington, Marcus; Jowza, Maryam; Waldman, Seth; Gay, Geri; Reid, M. Carrington
Abstract : Objectives: To examine preliminarily the effectiveness of a short message service (SMS) text message–based social support intervention for reducing daily pain and pain interference levels, improving affect and perceptions of social support in patients with chronic noncancer pain, and exploring the feasibility of a novel mobile application to track perceptions of pain and pain interference. Materials and Methods: Participants (17 men, 51 women) from 2 pain clinics in New York City downloaded a pain tracking application (App) on their Smartphone and used it to record twice-daily pain, pain interference, and affect scores over the 4-week study period. Participants were randomly assigned to receive standard care (control) or standard care along with receipt of twice-daily supportive SMS text messages delivered during the second and third week of the study (intervention). Demographic and clinical data were obtained at baseline, and social support measures were administered at baseline and at 4 weeks. Statistical analysis was carried out using general linear mixed models, taking into account variances associated with time of assessments and with patients. Results: The social support intervention reduced perceptions of pain and pain interference and improved positive affect for chronic noncancer pain patients assigned to the intervention condition in comparison with controls. Participants completed approximately 80% of the daily measurements requested. Discussion: These findings establish the feasibility of collecting daily pain data using a mobile tracking App and provide significant implications and insight into a nuanced approach to reducing the daily experience of pain through mobile technology, especially because of its accessibility.